CS-ENRICHED MINERALS AND THEIR SIGNIFICANCE ON NUCLEAR WASTE DISPOSAL - Hu H.; Wang R.; Xu S.; Zhang A. (My University, 2006)
Pollucite, Cs-analogue of micas and Cs-enriched beryl are the common Cs-enriched minerals in nature. They all occur in the central part or exocontact wall rocks of the rare-element granites and LCT (Lithium-Cesium-Tantalum)-type pegmatites. The presence of Cs-enriched minerals suggests they should crystallize in the primary granitic melts with cesium and volatile in origin which undergo the high to extreme degrees fraction in a stable tectonic environment. Cs concentration in Cs-enriched minerals are above 15%, so their synthetic phases are considered to be the potential containers of radioactive isotope 137Cs in the nuclear waste, and the mineralogical characteristics of Cs-enriched minerals, such as chemical composition and crystal structure, have a good significance on the selection of the container of 137Cs in the nuclear waste, the selection of the deep-bury geological environment and the prediction of the synthetic phases' behavior in different geological environment.
Keywords: CS-ENRICHED MINERALS; MINERALOGICAL CHARACTERISTICS; NUCLEAR WASTER DISPOSAL